Mobile phone based Deaf Sign Language Repository System / Sufiah Mohamed Amran - Mohamed Amran, Sufiah (2014)
In this day and age, there are many types of mobile application project can be develop using a several authoring tools. Multimedia elements such as text, graphic, audio and animation are integrated to build an interactive application environment to users. This paper describes a Mobile Phone based on Malaysian Deaf Sign Language Repository System. There are problem on most of hearing people lack of knowledge on how to use proper sign language to communicate and also limitation of sign language interpreter. The lack of service that facilitate a sign language leads to issues on most of hearing people have difficulties to communicate well with deaf people they also lack of knowledge about sign language. Basically, this project will provide a basic sign language that is alphabets A to Z and numbering, also the main focus of this application to allow a real time translation from alphanumeric text to sign language. The objectives of this project are to design a repository system of sign language based on mobile application also to develop repository system process of sign language for adults. And lastly to test the user satisfaction of sign language repository system based on mobile application whether it gives impact to the users. While for project methodology refers to previous research that similar to this development and then new methodology is created by considering all the limitation. Moreover, the development of mobile application is using Eclipse Android SDK that support android platform. For experimentation of the project, survey are performed as to gather user's feedback regarding use of mobile application and result that gathered get are highly positive that it will help to achieve the project objectives. The mobile application can be used as assistant whether anywhere and anytime also to improve knowledge on sign language as much as possible.